2000
DOI: 10.1054/jhsb.2000.0412
|View full text |Cite
|
Sign up to set email alerts
|

Severe Dupuytren's Contracture of the Proximal Interphalangeal Joint: Treatment by Two-Stage Technique

Abstract: Thirty-four patients with a Dupuytren's contracture in excess of 70 degrees of the proximal interphalangeal (PIP) joint were treated by preliminary palmar fasciotomy, release of the accessory collateral ligaments and PIP joint distraction using the S-Quattro for 6 weeks. A formal fasciectomy with full thickness skin graft was then performed 2 weeks after removal of the fixator. There was a mean residual flexion deformity of the PIP joint of 22 degrees (mean correction of 67 degrees) at an average follow-up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…Acute single stage correction of severe contractures may be compromised by the stretching of the neurovascular structures. Skeletal traction has been employed pre-and postoperatively using an external fixation device to improve correction of the PIPJ (Beard and Trail, 1996;Hodgkinson, 1994;Messina and Messina, 1993;Rajesh et al, 2000). In such cases, it has been demonstrated that as well as decreasing deformity, facilitating surgery, and foregoing the need for amputation, the traction also alters the metabolism of the fascia, which results in remodelling and consequent lengthening (Bailey et al, 1994;Brandes, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Acute single stage correction of severe contractures may be compromised by the stretching of the neurovascular structures. Skeletal traction has been employed pre-and postoperatively using an external fixation device to improve correction of the PIPJ (Beard and Trail, 1996;Hodgkinson, 1994;Messina and Messina, 1993;Rajesh et al, 2000). In such cases, it has been demonstrated that as well as decreasing deformity, facilitating surgery, and foregoing the need for amputation, the traction also alters the metabolism of the fascia, which results in remodelling and consequent lengthening (Bailey et al, 1994;Brandes, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…All patients achieved full correction of the deformity over a short period of time, even in patients with recurrent Dupuytren disease. It is 'low tech', does not require bulky and expensive external fixators, and can be applied without fluoroscopic guidance or regional anesthesia, unlike some other methods described (3)(4)(5)7). We believe that this modification offers the advantages of the method described by White et al (7), while being easier and less resource intensive that the original description.…”
Section: Discussionmentioning
confidence: 90%
“…This can have consequences for the stability of the joint and the functional status of the hand. Various regimens have been described including static splinting (2), dynamic splinting (3)(4)(5) or a combination of the two (6). We describe our experience of using a modification of pins and rubber band traction (PRBT) -a method of applying a dynamic extension apparatus to a contracted PIPJ that makes use of the constant traction force in a stretched rubber (elastic) band as described by White et al (7), and report our results in the treatment of contracted PIPJs in the hand.…”
mentioning
confidence: 99%
“…Dupuytren's disease (DD) is a heritable fibroproliferative and myofibroblastic disease that affects the palmar fascia and superficial palmar tissues of the hand and digits. [1][2][3][4] A subset of affected individuals who develop the earliest clinical sign of DD, myofibroblastic nodules, will progress to palmar-digital contractures that impose permanent loss of hand function. A predisposition to develop DD appears to be inherited in an autosomal dominant pattern [5][6][7] and, while disease incidence is historically highest amongst people of European ancestry, this association may be biased by the lack of detailed epidemiological studies in other regions.…”
Section: Introductionmentioning
confidence: 99%